Women's Empowerment in the Family Economy: The Role of Informal Education as a Catalyst for Gender Justice and Equality - Heryanto Susilo; I Ketut Atmaja Johny Artha; Ali Yusuf; Shobri Firman Susanto; M Fahmi Zakariyah (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the role of informal education in empowering women in the rural informal sector, thereby improving family economic conditions and promoting gender equality. Using a qualitative approach with a phenomenological method, the research was conducted in the Menganti District, Gresik Regency, involving women working in informal sectors. Data was collected through in-depth interviews, field observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that informal education through skills training, such as salted egg production and coconut shell charcoal processing, successfully enhanced women's technical skills, increased family income, and strengthened their self-confidence. Informal education also fostered social solidarity within the community, although women continued to face the double burden of balancing domestic responsibilities and economic activities. These results emphasize that informal education is not only a means of improving economic capacity but also catalyzes a shift in social values toward justice and gender equality. Women's empowerment through education must be accompanied by broader social structural changes and sustainable policy support to achieve inclusive and equitable development goals. Keywords: informal, women's empowerment, family economy, gender equality